ENT 530 Business Modal Canvas: Greeny Chill / Syed Ahmad Mujahir Syed Abdullah ... [et al.] - Syed Abdullah, Syed Ahmad Mujahir; Mohammad Norhan, Nurul Adlina; Mazlan, Muhammad Nur Akashah; Khairulhisyam, Farhah Nabilah; Rohizat, Nurizureen Nazira (2021)
Greeny Chill is a form of business based on a partnership which consists of five members who hold an important position such as General Manager, Administration Manager, Marketing Manager, Operational Manager, and Financial Manager. The business capital has amounted to RM250,000 where the contribution of each member is RM50,000. This company can be divided into 2 industries which are drinks and services. Those industries are two of the largest industry in the world because people are always going get foods and get drinks. Thus, it makes a never-ending demand for the products where people will continuously crave for them. Greeny Chill, with the motto of ‘A fresh drink for a wealthy mood’ is based in Setia Alam, Selangor. This company focuses on providing healthy juices and refreshment drinks. Greeny Chill also offer drinks and refreshment served in a self-serve drink machine. To make it more convenient, we are focusing on the usage of edible cups and straws in order to reduce the usage of plastic cups. The edible cups and straws are made from candy and jellies that comes from four distinct flavors. These edible cups are safe to be eaten and environmentally friendly. This study addresses the value of the business model canvas based on the information regarding Greeny Chill. The canvas elements have included customer segments, customer relationship, value proposition, channels, key activities, key resources, key partnership, cost structure and revenue stream.